1977
DOI: 10.1139/v77-512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of natural gas hydrates by nuclear magnetic resonance and dielectric relaxation

Abstract: Continuous-wave proton nmr spectra of the clathrate hydrates and/or deuteriohydrates of methane, ethane, propane, isobutane, and neopentane–D2S have been recorded down to 2 K. Between 50 and 200 K each H2O hydrate spectrum consists of a line 3 to 4 G wide from reorienting guest molecules and a broader band from rigid water molecules. Line shapes characteristic of non-rotating guests are obtained in D2O hydrates at low temperatures, except for methane which gives a narrow line to 2 K. Neopentane, shown for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…But as n-butane was verified as structure II former the shape of the molecule must also play a certain role. From dielectric [20] and Raman measurements [21] and recently single crystal X-ray diffraction [16] it was shown that n-butane is incorporated into the hydrate cage as its gauche conformer.…”
Section: Guest Molecule Diametermentioning
confidence: 99%
“…But as n-butane was verified as structure II former the shape of the molecule must also play a certain role. From dielectric [20] and Raman measurements [21] and recently single crystal X-ray diffraction [16] it was shown that n-butane is incorporated into the hydrate cage as its gauche conformer.…”
Section: Guest Molecule Diametermentioning
confidence: 99%
“…The clathrate hydrates behaviour has therefore been investigated, among other techniques, by Raman (e.g. Sum et al 1997) and (far-)infrared (Richardson et al 1985;Klug & Whalley 1973;Bertie & Jacobs 1982;Fleyfel & Devlin 1988) spectroscopies, as well as neutron scattering (Gutt et al 2002;Prager & Press 2006) and RMN techniques (Kleinberg et al 2003;Nakayama et al 2003;Davidson et al 1977). Pure methane hydrate forms cubic structure I, with two small watermolecule pentagonal dodecahedron cages (S = 5 12 ) and six large hexagonal truncated trapezohedron cages (L = 5 12 6 2 ) in the unit cell, with the general formula (2S.6L.46H 2 O).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reports on the spectra of methane, ethane, propane, and isobutene hydrates by Davidson and Garg and their co-workers, [141,142] NMR has been frequently used to determine the structure identification, chemical composition, cage occupancy, and water mobility in gas hydrates, and more recently the magnitude of spin-spin and spin-lattice interactions of gas hydrates, the character of relaxation processes, and their dependence on temperature and pressure. It has also been used to examine various defects, thermal fluctuations, translation, and rotation of molecules in gas hydrates, and to identify the enclathrated guest molecules and their concentrations.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%